Intravital multiphoton imaging of the selective uptake of water-dispersible quantum dots into sinusoidal liver cells - Liang, X.; Grice, J.; Zhu, Y.; Liu, D.; Sanchez, W.; Li, Z.; Crawford, D.; Le Couteur, D.; Cogger, V.; Liu, Jian; Xu, Z.; Roberts, M. (Wiley, 2015)
© 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim. Although many studies reporting the organ-level biodistribution of nanoparticles (NPs) in animals, very few have addressed the fate of NPs in organs at the cellular level. The liver appears to be the main organ for accumulation of NPs after intravenous injection. In this study, for the first time, the in vivo spatiotemporal disposition of recently developed mercaptosuccinic acid (MSA)-capped cadmium telluride/cadmium sulfide (CdTe/CdS) quantum dots (QDs) is explored in rat liver using multiphoton microscopy (MPM) coupled with fluorescence lifetime imaging (FLIM), with subcellular resolution (1 µm). With high fluorescence efficiency and largely improved stability in the biological environment, these QDs show a distinct distribution pattern in the liver compared to organic dyes, rhodamine 123 and fluorescein. After intravenous injection, fluorescent molecules are taken up by hepatocytes and excreted into the bile, while negatively charged QDs are retained in the sinusoids and selectively taken up by sinusoidal cells (Kupffer cells and liver sinusoidal endothelial cells), but not by hepatocytes within 3 h. The results could help design NPs targeting the specific types of liver cells and choose the fluorescent markers for appropriate cellular imaging. Spatiotemporal disposition of water dispersible quantum dots (QDs) is explored in liver in vivo using multiphoton microscopy with fluorescence lifetime imaging. After intravenous injection, negatively charged QDs are distributed in the sinusoids and selectively taken up by sinusoidal cells, while fluorescent molecules (rhodamine 123 and fluorescein) are taken up by hepatocytes and excreted into the bile.